Crisis and Reform in the Nigerian Oil Industry, 1999-2015 - Oyeranmi, Olusoji Samuel (NIU Journal of Social Sciences, 2020)
Despite the wealth flowing into the country from oil revenues many of Nigeriaâ€™s socio-economic factors were worse between 1999 and 2015 than they were several decades before the era. According to the World Bank, most of Nigeriaâ€™s oil wealth gets siphoned off by 1% of the population. Corruption in the government is rampant, in fact since 1960 it is estimated that 300 to 400 billion dollars has been stolen by corrupt government officials. As the government officials in connivance with the Multinational Oil Corporations siphon off much the money generated from oil sales the economy suffers and the people bear untold hardship. It is as a result of the above mentioned catastrophic consequences that this paper concludes that rather than being a blessing to Nigerians, Oil  has  become a curse because the oil sector of the country â€œis killing the economyâ€ almost  the same way it is impoverishing the people. But all hope is not lost if the stakeholders could come up with serious agenda towards reforming the sector. As a modest contribution to efforts at transforming the sector, with a focus on between 1999 and 2015, this paper critically analyses issues that are generating crises and offer some pragmatic ways to reform the Nigerian oil sector to serve greater interest of the economy and the people.                 Keywords: Oil, Nigeria, Corruption, Economy, Hardship, Stakeholders, Reform, People